Sociodemographic Differences in Intimate Partner Violence Prevalence, Chronicity, and Severity Among Young Sexual and Gender Minorities Assigned Male at Birth: The P18 Cohort Study - Stults, Christopher B. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is prevalent among young sexual and gender minorities assigned male at birth (YSGM-AMAB). However, few studies have examined the chronicity or distinguished between minor and severe forms of IPV among YSGM-AMAB. Furthermore, while past research has documented differences in IPV by race/ethnicity, sexual identity, gender identity, income, and education in other populations, few studies have examined these sociodemographic characteristics in relation to IPV in YSGM-AMAB. Thus, the present study aims to: (1) estimate past year prevalence and chronicity of minor and severe forms of IPV victimization and perpetration in a diverse sample of (N = 665) YSGM-AMAB in New York City, and (2) examine differences in IPV prevalence and chronicity by the aforementioned sociodemographic characteristics. Cross-sectional data from [BLINDED] informed these descriptive and inferential analyses. Nearly half of all participants reported past year IPV victimization and approximately 40% reported perpetration. Psychological violence was the most common form of victimization, followed by sexual, physical, and injury victimization. Psychological violence was the most common form of perpetration, followed by physical, sexual, and injury perpetration. Regarding sociodemographic differences in last year IPV prevalence, bisexual, transgender, and lower income YSGM-AMAB were more likely to report several subtypes of IPV victimization. Whereas Asian/API, bisexual, transgender, and lower income participants were more likely to report several subtypes of IPV perpetration. Regarding last year IPV chronicity, non-graduate YSGM-AMAB reported more instances of two subtypes of IPV victimization, while Black, White, cisgender, upper income, non-graduate participants reported more instances of several subtypes of IPV perpetration. These findings may be used to develop IPV prevention and intervention programs, inform future research endeavors, and develop and strengthen policies that reduce sociodemographic inequalities and promote more favorable sociopolitical conditions for YSGM-AMAB.